Assessment of the risk of falls and balance in climacteric women - Xavier, Patrícia Francieli de Paula (2018)
The objective of the study was to evaluate the balance and risk of falls of active and sedentary women in the climacteric period. A total of 14 women, aged between 45 and 80 years, participated in the study. The Berg’s Balance Scale and the Tinetti Index were used. The results showed that the static and dynamic balance is greater and the risk of falls is lower for physical activity practitioners. Conclude that the practice of physical activity tends to reduce the risk of falls, improves balance and functional aptitude, bringing great health benefits.Keywords: Menopause; Physical Activity; Balance; Climacteric.